Pengaruh Customer Experience, Electronic Word Of Mouth (E-Wom), Dan Cafe Atmosphere Terhadap Keputusan Pembelian Konsumen Di Warung Saro Sanur - Dhuaja, Ida Bagus Ary Indra; Sunia, I Wayan; Lestari, Ni Putu Nina Eka (AKADEMIK: Jurnal Mahasiswa Ekonomi & Bisnis, 2026)
The increasing competition in the food and beverage (F&B) industry requires businesses to create a distinctive and satisfying experience for customers. Warung Saro Sanur, a local restaurant combining modern and traditional concepts, strives to enhance its customer experience through interior design, service quality, and consistent product standards. This study aims to examine the influence of Customer Experience, Electronic Word of Mouth (E-WOM), and Café Atmosphere on Consumer Purchase Decisions at Warung Saro Sanur. The research applied a quantitative approach with a sample of 75 respondents determined using Ferdinand’s sampling formula. Data were collected through observation, documentation, and questionnaires, and analyzed using multiple linear regression with SPSS version 26. The findings indicate that Customer Experience, E-WOM, and Café Atmosphere each have a positive and significant effect on consumer purchase decisions, both partially and simultaneously. The coefficient of determination (R²) shows that 77.2% of consumer purchase decisions are explained by the three variables. These results suggest that creating a pleasant café environment and encouraging positive online reviews can strengthen consumers’ purchasing intentions and enhance brand loyalty in the F&B sector.